Investigation of Urban Community Lifestyle Carbon Footprint: A Case Study of Balikpapan Regency Housing - Rahmat Aris Pratomo; Ariyaningsih Ariyaningsih; Riyan Benny Sukmara; Nadia Nur Mahardhika; Muthya Karina Amalia; Berly Gizela Pramesti (Jurnal Geografika (Geografi Lingkungan Lahan Basah), 2025)
Human activities, particularly those related to energy consumption, mobility, and dietary patterns, are primary contributors to carbon emissions. Previous research indicates that the global composition of greenhouse gas (GHG) emissions is predominantly influenced by food (approximately 20%), housing (19%), and mobility (17%). In Indonesia, the transportation and housing sectors are recorded as major contributors to emissions. Balikpapan City, as an economic growth center in East Kalimantan, is experiencing rapid urbanization, marked by the development of large-scale residential areas. One such example is the Balikpapan Regency Housing Complex, where the community tends to exhibit high household energy consumption patterns, dependence on private transportation, and urban dietary consumption trends. This study aims to identify the extent to which lifestyle factors, particularly in the domains of mobility, housing, and food, contribute to carbon emissions. The research involves primary data collection through the distribution of questionnaires. A quantitative approach is employed, analyzing the carbon footprint over the past year across the domains of mobility, housing, and food. The results indicate that the housing domain is the highest contributor to the carbon footprint in the Balikpapan Regency Housing Complex